Enhancing merchant participation in QRIS adoption through digital marketing strategies: A case study of BPD Kaltim Kaltara in festival events - Rafif Leksono, Agra; Hidayat, Anas (Universitas Ahmad Dahlan, 2025)
In Indonesia’s accelerating digital economy, the promotion of cashless payments is central to advancing financial inclusion, particularly through the Quick Response Code Indonesian Standard (QRIS). Despite its growing use, many micros, small, and medium enterprises (MSMEs) remain hesitant to adopt QRIS due to limited digital literacy and trust in digital transactions. This study investigates how PT Bank Pembangunan Daerah Kalimantan Timur and Kalimantan Utara (BPD Kaltim Kaltara) employs digital marketing strategies to increase merchant participation in QRIS during festival events. Adopting a qualitative case study design, data were collected through semi-structured interviews with seven BPD marketing staff and participating vendors, complemented by secondary documentation. The findings reveal that digital marketing, through social media outreach, incentive programs, and integration with the DG by Bankaltimtara application, enhances awareness and engagement. However, adoption is hindered by obstacles such as low digital literacy among older merchants, skepticism regarding transaction security, and infrastructural limitations. These challenges underscore the limited effectiveness of current strategies in reaching all merchant segments. The study concludes that fostering QRIS adoption requires not only promotional efforts but also sustained education, technical assistance, and collaborative partnerships tailored to MSME needs. Theoretically, the research contributes to the discourse on digital marketing and innovation diffusion by highlighting the role of context-specific strategies in financial technology adoption. Practically, it offers insights for policymakers and financial institutions to design more inclusive, trust-building approaches that advance Indonesia’s digital financial ecosystem.